Dissociable neural correlates of item and context retrieval in the medial temporal lobes - Wang, Wei-chun (2013)
Although it is generally accepted that the medial temporal lobe (MTL) is critical for episodic memory, the contributions of cortical regions in the MTL, such as the perirhinal (PRc) and parahippocampal (PHc) cortices, remain unresolved. Recent studies have asserted that the PRc supports the processing of object and face information, whereas the PHc supports the processing of scene information. These findings have been used to characterize the PRc and PHc as being important for the memory of objects and scenes, respectively. However, these results are also consistent with the idea that these MTL regions are critical for the memory of stimuli that are processed as either items or contexts. It has been difficult to differentiate between these two accounts given that in most studies, item and context are operationalized as different types of memoranda (e.g., memory for objects compared to memory for background scenes). Here, we tested the extent to which different MTL regions are involved in the retrieval of item or context information when the material type is held constant. Participants encoded pairs of fractal images and were oriented to encode one fractal as an item and the other as a context. At test, they were cued with previously studied item or context fractals and asked to retrieve the corresponding associate. Results indicated that on test trials, PRc activity was increased during recall of fractals that were encoded as items, whereas PHc activity was greater during recall of fractals that were encoded as contexts. These results provide direct evidence that, even when stimulus type is held constant, the PRc and PHc are preferentially involved in supporting memory for item and context information, respectively.